1993
DOI: 10.1055/s-0038-1649638
|View full text |Cite
|
Sign up to set email alerts
|

Continuous Registration of Thrombin Generation in Plasma, Its Use for the Determination of the Thrombin Potential

Abstract: SummaryA method is described by which the time-course of thrombin generation in plasma can be obtained from a continuous optical density recording of p-nitroaniline (pNA) production in a 2:3 diluted plasma. A chromogenic substrate, methylmalonyl-methylanalyl-arginyl-pNA (SQ68), is used that is specifically split by thrombin but at a low rate. The thrombin that appears and disappears in the plasma does not split more than 5% of the substrate added, so the rate of substrate conversion is in good approximation pr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

6
285
1
9

Year Published

2003
2003
2015
2015

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 326 publications
(301 citation statements)
references
References 12 publications
6
285
1
9
Order By: Relevance
“…Although it was developed half a century ago [1,2], it is only during the last one and a half decade that the thrombin generation test has attracted increasing attention. It appears that this test may replace coagulation based tests in many cases in the future [3,4], more so as computer aided models of the events leading to coagulation have been developed and been shown to correlate well with biochemical observations [5,6].…”
Section: Introductionmentioning
confidence: 99%
“…Although it was developed half a century ago [1,2], it is only during the last one and a half decade that the thrombin generation test has attracted increasing attention. It appears that this test may replace coagulation based tests in many cases in the future [3,4], more so as computer aided models of the events leading to coagulation have been developed and been shown to correlate well with biochemical observations [5,6].…”
Section: Introductionmentioning
confidence: 99%
“…To mimic this process, several laboratory techniques have been devised including the thrombin generation time (TGT) and endogenous thrombin potential (ETP). (46,47) Employing such techniques, it has been shown that the amount of thrombin generated is also dependent on the concentration of prothrombin in plasma. This effect is primarily based on an increase in the peak of thrombin produced and not on any change in the rate of thrombin formation.…”
Section: Introductionmentioning
confidence: 99%
“…1 from left to right). Defibrination with Arvin is known to precipitate fibrin but not otherwise to affect the clotting system [14].…”
mentioning
confidence: 99%